Finding the needle in haystack of questions: ECMO in hypoxemic respiratory failure - K Guru, Pramod; Kumar Sahoo, Tapas (Journal of Nepalese Society of Critical Care Medicine, 2023)
Extracorporeal membrane oxygenation (ECMO) has gained significant attraction as a supportive measure for severe cardio-respiratory failure over the past decade and a half. Despite advances in the management of acute respiratory distress syndrome (ARDS) and its associated respiratory failure, there remain challenges for researchers and clinicians. Lung-protective mechanical ventilation and fluid restriction are widely accepted strategies for ARDS care. However, the precise role of ECMO in managing ARDS patients remains to be clearly defined. ECMO offers a potential solution for the hypoxemia and hypercapnia that arise from respiratory failure through its extracorporeal principles. Recent technological advancements have contributed to the widespread use of ECMO in critical care medicine. Nevertheless, several questions regarding its optimal application persist, with patient-centered outcomes at the forefront of care delivery. The discussion regarding the details of physiological principle underlying ECMO, various cannulation strategies, and monitoring approaches is beyond the scope of this review. In this article, we aim to provide valuable insights and address relevant queries pertaining to the optimal use of ECMO in critical care medicine.